Estratégias organizacionais e gestão por competência: estudo de caso em operadora de plano de saúde de Fortaleza-CE - Albuquerque, Renata Cavalcante (2010)
Currently, the management for abilities comes being considered for many organizations as being an efficient tool in the process of management of talents in an organization. In such a way, for the area of human resources, the management for abilities, can constitute, depending on the form as it is spread out, a strong allied for the reach of the organizational strategies. Based in the methodology to quadripolar of DeBruyne, Herman and Shoutheete (1977) the present work deals with the integration between the strategical management and the management for abilities, searching to identify the existing alignment between the professional abilities and the organizational strategies of a health operator. The first polar region, the epistemological, turns on Epistemology of Bachelard (1996), explicit the problematic involves the categories of the research: strategies and abilities, its origins and historical trajectory. The theoretical polar region deals with the construction of concepts and the main theories of strategies and abilities approaching following authors Kaplan and Norton (1997) in strategy, Mc Clelland (1973); Prahalad and Hamel (1990); Shultz (1950) and Penrose (1959), in abilities. The morphological polar region articulates the concepts, the theories and the models of the object in projects or clarifying and interpretative systems, where the models of Kaplan and Norton are illustrated (1997), Gramigna (2007) and Helm and Wasp (2008). The last polar region, the technician, shows the field research, controls the collection of data, it strengthens to evidence them and to collate them with the theory that excited itself. The related study it was become fullfilled through a descriptive research, approaching aspects quantitative. The research assumed the form of study of case, carried through in a medical cooperative installed in the city of Fortaleza CE. As instrument of support for the accomplishment of the case study the questionnaire, applied with fifty seven managers was used. The results of the research had shown in the perception of the managers, agreement exists enters the abilities adopted for the strategical operator and its pointers, being the organizational abilities the ones that are in bigger tunning with these pointers. The results had shown despite relations between the strategical result of the evaluation of performance of the company and its existed pointers, being able, therefore, to conclude that the management for abilities adopted by the health operator is lined up to its strategical management.